ANALISIS KEMAMPUAN MENYELESAIKAN SOAL HIGHER ORDER THINKING SKILLS SISWA KELAS XI SMA NEGERI 1 TANA RIGHU TAHUN AJARAN 2020 - Felisia Umbu Warata; Edi Wahyudi; Wilhelmus Yape Kii (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2020)
This study aims to determine the ability of students to solve higher order thinking skills questions. the type of research used is a quantitative descriptive approach using the polya model. Data retrieval is done by using the HOTS indicator, namely: Analyzing, Evaluating, Creating. Data collection techniques used are written test methods. The results of this study were seen from one item analyzing items, one item evaluating questions, one item creating and can be seen from the results of students` ability to solve higher order thinking skills polya steps. Based on the three items of questions namely the problem of analyzing, evaluating, creating can be seen the ability to think high-level students with a percentage of the aspect of analyzing the stage of understanding the problem reached 80%, the stage of planning the completion of 66,7%, the stage of implementing the plan reached 60%, and the stage of checking again reached 13,3%, evaluating aspects at the stage of understanding the problem 66,7%, the stage of planning the completion reached 60%, the stage of implementing the plan reached 53,3%, the rechecking stage reached 6,7%, the creating aspect at the stage of understanding the problem reached 53,3%, the stage of planning the completion reaches 0%, the stage of implementing the plan reaches 0%, and the stage of re-checking 0%